Determination of intervention to improve food allergy knowledge among Malaysians - Mohamed, Rosmaliza; Ramli, Kamal Izzuwan; Rashid, Basri; Din, Norrina (2018)
The population of food allergy sufferer world wide keep on increasing especially among children. Therefore, while the parent is working, this children is taken care by the nursery employees. Since there is no cure for food allergy, the nursery employees need to be knowledgeable to provide safe food and environment to them. For that reason, this study aims to determine the types of intervention that can help the nursery employees to improve their knowledge. This study is crucial to create awareness and protect this susceptible population to stay healty.